Justification of cyber-harassment in terms of digital media literacy [Bilişim okuryazarlığı bağlamında siber şiddetin meşrulaştırılması] - (:unkn) unknown (Istanbul Universitesi, 2016)
Objective: Violence and the media are an important issue that takes up a large part in media theories and research. The interaction between the individual and the society and the phenomenon of violence which can be increased or normalized can be examined and discussed not only in the media axis but also in many other disciplines in terms of different variables. Though it is unlikely to be the only factor affecting the phenomenon of violence, media tools and developments in technology have now caused violence to be debated in different dimensions. In this research, the effects of the concepts of information literacy, cyber violence and emotional deafness (alexithymia) on the perception of individuals as violating legitimacy are discussed as factors that cause individuals to perceive violence as legitimate through communication means. Method: Present research was conducted with 400 university students by survey methods. Results: Data was analyzed in SPSS computer program. According to the results it was determined that variables of cyber violence exposure, perpetrator of cyber violence, digital media literacy and alexithymia (emotional deafness) were explanatory effects on justification of cyber harassment. Conclusions: In this context, it has come to the point that the digital media literacy and conscious internet usage are important in order to prevent individuals from seeing cyber violence as legitimate and justification of it. © 2016, Istanbul Universitesi. All Rights Reserved.
Keywords: Alexithymia; Cyber-harassment; Digital media literacy; Justification of cyber-harassment